Family History-Taking in Paediatrics: It's Much More Than Just A Checklist. (1st June 2016) - Tessier, L; Brehaut, J; Potter, B; Chakraborty, P; Carroll, J; Wilson, B
Abstract: BACKGROUND: Family history (FH) is a risk factor for many conditions in pediatric practice; interest has increased in supporting systematic FH taking in this area by identifying core conditions for enquiry and developing point of care tools. There is little published about current practice to inform implementing such changes. OBJECTIVES: To inform future FH taking interventions by identifying pediatricians' perceptions, attitudes, beliefs, and current practices. DESIGN/METHODS: The Theoretical Domains Framework (TDF) was used to develop a comprehensive interview scheme. Semi-structured interviews were conducted with community and hospital-based pediatricians Analysis was by the constant comparison method, using a thematic approach. This study was funded by the Canadian Institutes of Health Research. RESULTS: The data revealed FH taking to be a firmly embedded, but complex aspect of pediatric practice. Participants described FH as part of regular, holistic care, extending to social and interpersonal, as well as clinical purposes; in addition to disease risk assessment, FH information helped clarify diagnosis, and select medication; tailor the overall patient management based on family circumstances; and provide psychosocial support for parents. It was also used as a method to build a relationship with parents/carers. FH and social history information were inextricably linked and often appeared to be the same concept in participants' minds. Participating pediatricians generally expressed confidence in their FH skills and reported tailoring their approach according to experience, after initial training early in their career. While acknowledging some challenges in ensuring accuracy, they were attuned to nuances in their interactions with parents and children which would affect whether, and what, they were told about illness in the family. Most were not concerned about formal evidence, and would not change their practice except for "good reason". CONCLUSION: The use of the TDF helped ensure a comprehensive approach to FH taking in pediatric practice. The findings suggest that FH taking in this setting is a complex activity, embedded in routine care. Recommendations for systematic enquiry about specific conditions cannot be seen as a simple additional activity to current practice. Efforts to make FH taking more systematic may founder if they fail to take into account pediatricians' attitudes, perspectives, and practices. Further studies should explore and seek to confirm and expand our observations.